2014
DOI: 10.1111/1756-185x.12283
|View full text |Cite
|
Sign up to set email alerts
|

Is the health-related quality of life and functional status of patients with psoriatic arthritis worse than that of patients with psoriasis alone?

Abstract: Patients with Ps and PsA had worse quality of life and patients with PsA had worse functional status than healthy individuals. Although Ps patients with arthritis had a worse functional status than the ones without arthritis, quality of life according to PSAQoL was found to be similar between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The prevalence of AS ranges from 0.02% to 0.35% worldwide, whereas the prevalence of PsA ranges from 0.01% to 0.19% [3] and can be up to approximately 40% in patients with psoriasis [2]. Both conditions negatively affect quality of life, physical and social functioning, and work productivity, in addition to being associated with comorbidities and increased mortality [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AS ranges from 0.02% to 0.35% worldwide, whereas the prevalence of PsA ranges from 0.01% to 0.19% [3] and can be up to approximately 40% in patients with psoriasis [2]. Both conditions negatively affect quality of life, physical and social functioning, and work productivity, in addition to being associated with comorbidities and increased mortality [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Tezel et al28 studied 80 patients with PA, 40 patients with Ps and 40 healthy subjects in terms of QoL and functional status and found that patients with Ps and PA had worse QoL and patients with PA had worse functional status than healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 HRQoL is an important outcome for daily practice and evidence based data; however, to our knowledge, limited number of publications are present regarding PsQoL questionnaires in PsA. [16][17][18][19] PsQoL questions social, psychological, and occupational issues but not physical functions. 17 Some authors pointed out that the questionnaire for PsQoL is not adequate for the evaluation of HRQoL of patients with PsA because this questionnaire does not include questions on basic dermatological clinical picture.…”
mentioning
confidence: 99%
“…[16][17][18][19] PsQoL questions social, psychological, and occupational issues but not physical functions. 17 Some authors pointed out that the questionnaire for PsQoL is not adequate for the evaluation of HRQoL of patients with PsA because this questionnaire does not include questions on basic dermatological clinical picture. 16,17,20 VITACORA-19 (psoriatic arthritis quality of life questionnaire) is the second diseasespecific patient reported outcome measurement tool to assess HRQoL in patients with PsA.…”
mentioning
confidence: 99%